SMART Bangladesh Vision 2041: Concept of a Sustainable Developed Country - Pal, Subrata Kumer; Sarker, Pramath Chandra (Environmental Management and Sustainable Development, 2023)
<span style="color: #000000; font-family: Verdana, Arial, Helvetica, sans-serif; font-size: 10px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;">A smart country or smart city is one of the key issues all over the world, some countries have projected and some are trying to be smart. In the same way, the present government of Bangladesh wants to develop the country to the stage of a developed and sustainable country through the new concept of ’Smart Bangladesh’ by 2041. The recent development plan is a part of the present Bangladesh government’s development agenda widely known as "Smart Bangladesh Vision 2041". This slogan has already attracted a large part of the population (mainly the young citizens) like "Digital Bangladesh". For this reason, the government has taken many inclusive initiatives combining people, government, economy, society and cities. This research paper represents the concepts and key elements or main pillars of "Smart Bangladesh Vision 2041". Besides, it shows various initiatives taken by Bangladesh government for implementing this development plan. It is imperative to have clear, concrete, and conceptual knowledge of Smart Bangladesh for all stakeholders before implementing successfully an inclusive vision.